2006
DOI: 10.1371/journal.pmed.0030238
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Workplace HIV Counselling and Testing: A Cluster-Randomised Trial in Zimbabwe

Abstract: BackgroundHIV counselling and testing is a key component of both HIV care and HIV prevention, but uptake is currently low. We investigated the impact of rapid HIV testing at the workplace on uptake of voluntary counselling and testing (VCT).Methods and FindingsThe study was a cluster-randomised trial of two VCT strategies, with business occupational health clinics as the unit of randomisation. VCT was directly offered to all employees, followed by 2 y of open access to VCT and basic HIV care. Businesses were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 26 publications
(37 reference statements)
8
91
1
Order By: Relevance
“…Several studies in Zimbabwe have demonstrated failure of participants to access VCT when remote from the research setting. In a study where workplaces were randomised to either onsite VCT or vouchers for offsite testing, there was 51.1% uptake when VCT was offered onsite compared to 19.2% when offered offsite (Corbett et al, 2006). Offering VCT at the survey site did not add substantially to our research costs.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies in Zimbabwe have demonstrated failure of participants to access VCT when remote from the research setting. In a study where workplaces were randomised to either onsite VCT or vouchers for offsite testing, there was 51.1% uptake when VCT was offered onsite compared to 19.2% when offered offsite (Corbett et al, 2006). Offering VCT at the survey site did not add substantially to our research costs.…”
Section: Discussionmentioning
confidence: 87%
“…The self-testing approach offers distinct advantages. By giving people the opportunity to test discreetly and conveniently, self-testing may increase the uptake of testing among people not reached by other existing testing services many whom are first-time testers [204][205][206][207]. The experience with hepatitis self-testing is currently very limited, but it represents a potentially important approach to expand access to hepatitis testing in the future.…”
Section: Self-testingmentioning
confidence: 99%
“…Other factors associated with improved uptake include personal or professional interaction with an individual living with HIV/AIDS and having the choice to undergo VCTat the workplace or an offsite location [29,30]. In a study randomly assigning small and medium-sized companies in Zimbabwe to either on-site rapid HIV testing or vouchers for off-site VCT at a chain of freestanding centers, the mean uptake of workplace VCT by site was 51.1% compared with 19.2% mean uptake of offsite VCT over 2 years [34].…”
Section: Workplace Hiv Prevention Programmesmentioning
confidence: 99%